Pendampingan Modul Ajar Adaptif Dan Implementasi Smart Assessment Berbasis AI (Artificial Intelligence) Bagi Guru SMP Negeri 3 Medan - Ika Febriana; Nurul Azizah; Rosmaini (Inisiatif : Jurnal Dedikasi Pengabdian Masyarakat, 2026)
This community service activity aims to improve teachers' competence in compiling adaptive teaching modules and implementing Artificial Intelligence (AI)-based smart assessments for teachers of SMP Negeri 3 Medan. The problems faced by the partners include the limited competence of teachers in developing adaptive teaching modules based on differential learning and the Independent Curriculum, learning assessments that are still carried out conventionally, limited digital literacy and teachers' social readiness in utilizing AI technology, and the lack of innovation and collaboration based on digital technology in the school environment. Service activities are carried out with a participatory method through five stages, namely program socialization, training, application of learning technology, mentoring and evaluation, and program sustainability. This service activity was attended by 23 teachers of SMP Negeri 3 Medan. Training and mentoring are carried out by utilizing the Tegur application in the preparation of adaptive teaching modules and AI-based assessments. The results of the activity showed that there was an increase in teachers' understanding and skills in developing differential learning tools, conducting AI-based digital assessments, and utilizing technology to support more effective and data-based learning. Achievement indicators can be seen from the participants' activeness in asking questions and discussing, the teacher's ability to compile modules, and the use of AI applications in assessments. In addition, this activity also increases digital literacy, culture of enthusiasm, and teachers' readiness to face digital education transformation. Thus, this activity has positive implications for teachers' readiness to utilize AI technology and implement adaptive learning in schools.